2017
DOI: 10.1097/igc.0000000000000880
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Morbidity and Quality of Life in Cervical Cancer Survivors: A Multicenter Comparison Between Surgery and Radiotherapy as Primary Treatment

Abstract: Although global health scores are not significantly different, women after PRT report more physical, social, and sexual symptoms. These results can be well used by physicians to inform their patients about treatment-related morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 41 publications
1
41
1
3
Order By: Relevance
“…In a recent published study concerning morbidity and QoL after primary surgical or (C)RT for early-stage cervical cancer, we also described impaired social functioning, less sexual enjoyment, and higher symptom experience scores after primary (C)RT compared with patients with adjuvant (C)RT. 30 Although we did not report details about postoperative complications of the radical hysterectomy in this study, it is clear that severe bowel problems resulting from radiation enteritis are related to the surgery. On the other hand, as discussed previously, increased pelvic floor symptoms, such as fecal incontinence, are definitely more frequent after primary radiotherapy.…”
Section: Discussionmentioning
confidence: 86%
“…In a recent published study concerning morbidity and QoL after primary surgical or (C)RT for early-stage cervical cancer, we also described impaired social functioning, less sexual enjoyment, and higher symptom experience scores after primary (C)RT compared with patients with adjuvant (C)RT. 30 Although we did not report details about postoperative complications of the radical hysterectomy in this study, it is clear that severe bowel problems resulting from radiation enteritis are related to the surgery. On the other hand, as discussed previously, increased pelvic floor symptoms, such as fecal incontinence, are definitely more frequent after primary radiotherapy.…”
Section: Discussionmentioning
confidence: 86%
“…However, in published reports of a subgroup of patients in the here presented cohort, primary surgery with tailored adjuvant (chemo-)radiotherapy does not result in significantly more morbidity compared with primary (chemo-)radiotherapy. 36,41 Our study has important limitations. It speaks for itself that the retrospective character of the study can have inherent confounding.…”
Section: Discussionmentioning
confidence: 94%
“…11,14,35 On the other hand, more radical surgery might decrease the need for adjuvant radiotherapy resulting in less radiotherapy-related side effects. 21,36 This latter issue is especially important in the debate about primary surgery or primary (chemo-)radiotherapy in stage IB2 cervix cancer, where many studies are published reporting a very high rate of adjuvant radiotherapy. 37Y40 This combination may result in increased complication rates and morbidity resulting in the suggestion of many authors not to recommend primary surgery but primary chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Among which 64% were found to be sexually active, 67% responded with radical hysterectomy and 50% with primary radiation therapy. 26 However, our study also showed lower scores among patients treated with CCRT having social, functional and financial difficulties. Furthermore, Women treated with CCRT showed higher level of symptom experience, sexual or vaginal functioning as well as sexual worry.…”
Section: Preoperative Chemotherapy Armmentioning
confidence: 43%